Chemical Staining of Deodar Pencil Slats - Rehman, M. A.; Kishen, Jai (Indian Forester, 1953)
A cheap and simple method of staining pencil slats of deodar by the use of nitric acid is given. The Eastern red cedar of America (Juniperus virginiana) also called the American pencil cedar, is the most popular wood used in the manufacture of the writing pencils. Owing to over-exploitation, the supplies of this species are falling off. Other timbers used extensively in the pencil industry are the Californian incense cedar (Libocedrus decurrens) and the East African cedar (Juniperus procem). Both of these are, however, treated to improve their cutting qualities and colour. The treatment generally given consists of impregnating the seasoned slats with an aqueous solution of a suitable dye followed by softening with wax, or it consists of impregnation of slats with an aqueous emulsion of wax or oil to which suitable dye has been added. These treatments involve the application of vacuum as well as pressure, and the plant required is costly.